2018
DOI: 10.3390/lubricants6020040
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical Simulations of a Flexible Rotor in Cylindrical Uncavitated and Cavitated Lubricated Journal Bearings

Abstract: Due to requirements of their operating conditions, such as high speed, high flexibility and high efficiency, rotating machines are designed to obtain larger operating ranges. These operating conditions can increase the risk of fluid-induced instability. In fact, the presence of non-linear fluid forces when the threshold speed is overcome by the rotational speed, can generate rotor lateral self-excited vibrations known as "oil whirl" or "oil whip". These instabilities derive from the interaction between the rot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 22 publications
(29 reference statements)
0
8
0
Order By: Relevance
“…The research method used is to use CFD Fluent in ANSYS. The geometry parameters refer to the previous study in table 1, using secondary data from the previous study. The material Babbit alloy uses in bearings [16].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The research method used is to use CFD Fluent in ANSYS. The geometry parameters refer to the previous study in table 1, using secondary data from the previous study. The material Babbit alloy uses in bearings [16].…”
Section: Methodsmentioning
confidence: 99%
“…Journal bearings work only under limited conditions (metal-to-metal contact) during engine start-up and shutdown. Because there is often contact between the two, the lubrication must be good to minimize the occurrence of friction between the journal and the bearing, which results in damage to the journal bearing [1]- [4] Figure 1 shows the basic geometry of the journal bearing in a steady-state configuration. The hydrodynamic movement of the journal bearing causes pressure in the lubrication.…”
Section: Introductionmentioning
confidence: 99%
“…2019, 9, x FOR PEER REVIEW 2 of 15 successfully, the vibration amplitude of the system was reduced by 60%. Considering the effect of the cavitation, Ruggiero et al [4] found the "oil whirl" produced by the non-linear fluid forces. Wang [5] studied a controllable SFD for a rotor system and revealed its effect mechanism.…”
Section: Rotor Systemmentioning
confidence: 99%
“…Meanwhile, the obtained results were in agreement with the experimental results; when Coorper [3] presented the experimental study on SFD, and applied it to the Conway engine successfully, the vibration amplitude of the system was reduced by 60%. Considering the effect of the cavitation, Ruggiero et al [4] found the "oil whirl" produced by the non-linear fluid forces.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrodynamic journal bearings have been extensively used in heavy industry machines and turbomachinery [1] to support rotating shafts due to their superior durability, low maintenance cost, and excellent load carrying capacity [2][3][4][5][6]. Journal Bearings are critical components of the tools operating downhole, such as directional drilling (DD) tools that are used in oil and gas exploration and drilling applications.…”
Section: Introductionmentioning
confidence: 99%